2022
DOI: 10.1371/journal.pone.0264359
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of patients with cirrhosis presenting with bleeding gastric varices

Abstract: Aim To establish a therapeutic strategy for cirrhosis patients with gastric variceal bleeding. Methods The outcomes of 137 patients with bleeding gastric varices were evaluated. Results The bleeding source was gastroesophageal varices (GOV) in 86 patients, and gastric fundal varices (FV) in 51 patients. The Child-Turcotte-Pugh classes were A, B, and C in 26, 79, and 32 patients, respectively; 34 patients (24.8%) had hepatocellular carcinoma (HCC), of which 11 also had complicating portal venous tumor throm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
1
2
Order By: Relevance
“…The median survival time of our patients was more than 69 months which was better than the results of the previous studies (23,25,26). The in-hospital mortality rate immediately after the procedure was also much lesser in our patients (5.5%) than in the recent study from Japan (8.0%) (26).…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…The median survival time of our patients was more than 69 months which was better than the results of the previous studies (23,25,26). The in-hospital mortality rate immediately after the procedure was also much lesser in our patients (5.5%) than in the recent study from Japan (8.0%) (26).…”
Section: Discussioncontrasting
confidence: 68%
“…We found that the long-term survival rates of our patients were superior to that of a single-centre retrospective analysis that included 60 patients who received BRTO for gastric varices between December 2005 and September 2018, where the overall survival rate was 44.1% at ten years (23). The median survival time of our patients was more than 69 months which was better than the results of the previous studies (23,25,26). The in-hospital mortality rate immediately after the procedure was also much lesser in our patients (5.5%) than in the recent study from Japan (8.0%) (26).…”
Section: Discussioncontrasting
confidence: 51%
“…However, for striated varicose veins (mild to moderate) with a diameter less than 1 cm, precise puncture and precise endoscopic injection are difficult because of the low vascular tone. Therefore, rebleeding is characterized by bleeding from a draining ulcer that can develop as a result of TAI[ 21 , 22 ]. On the basis of our clinical findings, EBLs prevent bleeding from glue-draining ulcers.…”
Section: Discussionmentioning
confidence: 99%